EFFECT OF THREE PAKISTANI DATE-SEED VARIETIES ON LIPID PROFILE OF DIET INDUCED HYPERLIPIDEMIC RABBITS - Malik, Mahwash; Zaffar, Sehrish; Fatimah, Mufakhara; Chiragh, Sadia; Malik, Sarosh; Rehan, Abdul Mudabbir (Journal of Ayub Medical College Abbottabad, 2019)
Background: Hyperlipidemia is one of the major risk factors of cardiovascular diseases. In addition to current therapeutic strategies, a lot of work is being done on nutraceutical management of this condition. This study was designed to assess the effect of date seed powder on lipid profile of diet induced hyperlipidemic rabbits. Methods: Thirty male rabbits were divided into five groups, having six animals in each. One group was given normal rabbit chow throughout the study period of eight weeks. The remaining four groups were fed high fat diet (4% coconut oil and 1% cholesterol powder) for first four weeks in order to induce hyperlipidemia. After first four weeks, 2% date seed powder of three Pakistani varieties namely Dhakki, Khudrawi and Desi was added to the diet of three experimental hyperlipidemic groups for the next four weeks. Body weight and blood samples were taken at zero, 4th and 8th week of study. Serum was analyzed for total cholesterol, LDL-cholesterol, HDL-cholesterol and serum triglycerides. LDL/HDL ratio and AIP were calculated. Results: It was observed that date seed powder of the three varieties significantly decreased total cholesterol, serum triglycerides and AIP. There was no significant change in body weight, HDL-cholesterol, and LDL/HDL ratio. LDL cholesterol was decreased significantly only by Khudrawi date seed powder Conclusion: It was concluded that date seed powder has marked antihyperlipidemic properties. However, the difference in appearance, taste and price of different dates does not affect their lipid lowering capacity. Keywords: Hyperlipidemia; Date-seed, P.Dactylifera; lipid profile